MINIMIZING RESIDUAL STAND DAMAGE AND FELLING COST USING LOWEST POSSIBLE FELLING TECHNIQUE (A case study in one logging company in West Kalimantan) - Suhartana, Sona; Krisdianto, Krisdianto (Indonesian Journal of Forestry Research, 2005)
The implementation of felling technique in logging companies is not yet carried out efficiently and appropriately. Study on the lowest possible felling technique (LPFf) is considered  to be important to  reduce residual  stand damage and felling cost. This study was carried out in a logging company in West Kalimantan in 2004. The aim of this study was to  determine the effect of LPFT on residual stand damage and felling cost. Data collected in this research include: residual stand damage, working time, timber  volume, productivity,  efficiency,  stump   height  and  felling cost.  Two categories  data were analyzed with  respect  to  their  possible  differences  using  T-test.    The  result  showed  that  the implementation   of  LPFT  was more advantage impact compared  to   that of  conventional felling technique, which is  indicated by the following factors:  (1)  Trees damage decreased 2.96%;  (2) Poles damage decreased 4.75%;  (3) Felling productivity decreased 17.16%; (4) Felling efficiency  increased approximately  3.2%;  (5) Felling cost increased about Rp 327.07 /  m; and (6) in average stump height was 40.60 cm lower.